HISTORICAL AND PHILOSOPHICAL FACTORS IN THE FORMATION OF THE SPIRITUAL AND CULTURAL HERITAGE OF THE KARAKALPAK PEOPLE - Abdullaev, Makhset Jaksilikovich (SCIENCE and SOCIETY, 2026)
The article analyzes the historical, social, and philosophical factors that influenced the formation of the spiritual and cultural heritage of the Karakalpak people. It reveals the inseparable connection of the spiritual life of the Karakalpak people with the Turkic civilization, Islamic culture, and the local ethnocultural environment. Furthermore, the significance of oral folk art, traditions, and values in shaping national identity is substantiated from a socio-philosophical perspective.